PREDIÇÃO DA ÁREA DE DISTRIBUIÇÃO POTENCIAL DO TUCUNARÉ, Cichla monoculus Agassiz, 1831, NA BACIA AMAZÔNICA - PESSI, Lidiane Lima; SOUZA, Beatriz Cristina de Paula; BAILLY, Dayani; FERREIRA, José Hilário Delconte; OSÓRIO, Jeferson Mateus Barros; BATISTA-SILVA, Valéria Flávia (ANAIS DO ENIC, 2025)
-